THE CURRENT STATE OF ENVIRONMENTAL MANAGEMENT OF ENTERPRISES IN THE AGRICULTURAL SECTOR (ON THE EXAMPLE OF “KERNEL-TRADE” LLC) - Prus , Yu.I.; Patlakh , I.S. (The actual problems of regional economy development, 2023)
The article is devoted to the analysis of the current state of environmental management of agricultural enterprises (on the example of “Kernel-Trade” LLC). The article analyzes the indicators of development of certain types of economic activity in order to determine the place of agriculture in the economy of Ukraine. Using statistical data, the author assesses the impact of agricultural enterprises on the environment (the use of mineral and organic fertilizers, liming of soils, soil gypsumization, soil treatment with pesticides, etc.) The author assesses the volume of investments and current expenditures in the field of environmental protection of agricultural enterprises in Ukraine. “Kernel-Trade” LLC is considered as one of the strongest players in the agro-industrial market, and its main financial indicators (profit, EBIDTA, social payments, gross income, net debt), its contribution to the achievement of the UN Sustainable Development Goals (namely, contribution to Sustainable Development Goal 6 – clean water and satisfactory sanitation 7 – affordable and clean energy, 12 – responsible production and consumption, 15 – protection and restoration of terrestrial ecosystems, and 17 – partnership for sustainable development) and the environmental management cycle in the field of environmental protection. Based on the analysis of statistical information from the company’s annual report, the volume of CO2 emissions by different types of activities was compared. Using the SWOT analysis, the features of the current state of environmental management of the enterprise are summarized. The scientific novelty and theoretical significance of the article’s results lies in the development of theoretical and methodical provisions for improving the management of enterprise competitiveness through the implementation of environmental management initiatives. Today, the topic of ecology is extremely relevant, since obtaining EU membership requires not only economic and political changes, but also, above all, changes in the sustainable development of the country as a whole. It is through the prism of agriculture that the authors of the article emphasized the need for changes in the approach to enterprise management on the basis of environmental sustainability in Ukraine.